Role of single-ring oval disposable wound protecting device in preventing surgical site infection in laparoscopic colorectal resections - Prakash Kurumboor; Sidharth Chacko; I S Vipin; Rohan Prakash; Ashna S Pal (Journal of Minimal Access Surgery, 2024)
Context: Surgical site infections (SSI) continue to be a major cause of morbidity, mortality, prolonged hospital stays and a major reason of financial burden to health-care providers and patients after major abdominal surgeries. Along with infection control practices and care bundles, additional use of devices which protect the wound from contamination is believed to decrease the burden of SSI. Aims: This study aims to assess the benefit of single-ring disposable wound protector in preventing SSI, overall complications, hospitals stay and morbidity data in laparoscopic colorectal resection. Settings and Design: The study design involves case–control study, retrospective. Subjects and Methods: A case–control study comparing single ring oval wound protector versus conventional wound protectors retrospectively between August 2019 and December 2021. The ease of use of the device, rate of SSI, overall complications, hospitals stay and morbidity data were analysed. Statistical Analysis Used: The statistical analysis was performed by IBM SPSS Statistics 20 version. All Categorical Variables will be described as frequency and percentage. Continuous variables will be described as mean ± standard deviation. Continuous variables were analysed using t-test and categorical parameters using Fisher's exact test. Results: Of the 110 patients studied, wound Protecting devices were used in 58 patients Wound Protector Group (WPG group) and 62 patients did not use such devices (no WPG). The groups were comparable in demographic features, risk features, systemic illness, type of surgeries undertaken and the specimen extraction wound used. There was a significant decrease in the incidence of SSI (1.7% vs. 16% P ≤ 0.008) and the hospital stay (P ≤ 0.03) when WPG was used compared to the group in which it was not used. Conclusions: Apart from the use of infection control practices and care bundles, the use of oval-shaped single-ring wound protector is likely to reduce SSI.